2015
DOI: 10.1007/s00432-015-2031-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of metachronous contralateral breast cancer in the Canton of Zurich: a population-based study of the cancer registry

Abstract: PURPOSE To examine the incidence and characteristics of metachronous contralateral breast cancer (CBC) among women in the Canton of Zurich, Switzerland. METHODS For 1980-2006 with unilateral invasive breast cancer (UBC) were analysed for metachronous CBC. Poisson's regression was used to estimate incidence rates of metachronous CBC according to age, year of diagnosis, follow-up period since first breast cancer and morphology. RESULTS Of 16,323 patients with UBC, 700 (4.3 %) developed a second malignant tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…reported 10‐year cumulative metachronous CBC risks of approximately 4–5.5% in a large population based sample of over 85.000 women with previous invasive BC without distant metastases in Denmark . A population‐based study performed in Switzerland revealed a CBC incidence rate of approximately 4.5–5 per 1,000 PY after 4–11 years follow‐up, compared to 4.1 per 1.000 PY in our study after 5–10 years follow‐up . These results suggest that the CBC risk in our cohort of BRCA1/2 noncarriers is on average as high as in the general population.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…reported 10‐year cumulative metachronous CBC risks of approximately 4–5.5% in a large population based sample of over 85.000 women with previous invasive BC without distant metastases in Denmark . A population‐based study performed in Switzerland revealed a CBC incidence rate of approximately 4.5–5 per 1,000 PY after 4–11 years follow‐up, compared to 4.1 per 1.000 PY in our study after 5–10 years follow‐up . These results suggest that the CBC risk in our cohort of BRCA1/2 noncarriers is on average as high as in the general population.…”
Section: Discussioncontrasting
confidence: 47%
“…38 A population-based study performed in Switzerland revealed a CBC incidence rate of approximately 4.5-5 per 1,000 PY after 4-11 years follow-up, compared to 4.1 per 1.000 PY in our study after 5-10 years follow-up. 39 These results suggest that the CBC risk in our cohort of BRCA1/2 noncarriers is on average as high as in the general population. As a consequence, for this group of women and for women from the general population, the same intensity of surveillance measures might be recommended.…”
Section: Discussionmentioning
confidence: 55%
“…This very efficient method is rarely used to establish drug-drug interaction in cancer-related studies. Instead, usually simple-type associations between tested compounds are presented, where only one or few random chosen doses are selected, without precise method of drug-type interaction analysis [ 53 , 55 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important since, according to the existing literature, between 1.9% and 11.1% of women will have an ipsilateral breast cancer recurrence (median follow‐up 10.5 years) and between 1.1% and 8.3% of women will have contralateral breast cancer (median follow‐up 7.5 years) 16 . Our group has previously shown that of 16 323 patients with unilateral primary breast cancer diagnosed in the canton of Zurich between 1980 and 2006, 700 (4.3%) developed a second malignant tumor of the opposite breast 17 …”
Section: Introductionmentioning
confidence: 94%
“…16 Our group has previously shown that of 16 323 patients with unilateral primary breast cancer diagnosed in the canton of Zurich between 1980 and 2006, 700 (4.3%) developed a second malignant tumor of the opposite breast. 17 In this study, we aimed to identify important key characteristics for the prediction of a malignant SBC from readily available patient-level data and classify the patients as high or low risk for SBC. The small percentage of cases that need to be detected makes the data imbalanced, an aspect that together with missing values in potentially crucial predictors, is often neglected in the literature.…”
Section: Introductionmentioning
confidence: 99%